2013
DOI: 10.1371/journal.ppat.1003153
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Malaria Elicits Inflammatory Responses that Dysregulate Placental Amino Acid Transport

Abstract: Placental malaria (PM) can lead to poor neonatal outcomes, including low birthweight due to fetal growth restriction (FGR), especially when associated with local inflammation (intervillositis or IV). The pathogenesis of PM-associated FGR is largely unknown, but in idiopathic FGR, impaired transplacental amino acid transport, especially through the system A group of amino acid transporters, has been implicated. We hypothesized that PM-associated FGR could result from impairment of transplacental amino acid tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 67 publications
5
69
1
5
Order By: Relevance
“…Sequestering parasites release bioactive molecules that stimulate both maternal cells [4] and fetal syncytiotrophoblast [5, 6] to produce proinflammatory cytokines and chemokines, which in turn recruit, activate and retain inflammatory cells in the maternal intervillous space [4, 6-12]. Indeed, accumulation of maternal monocyte/macrophages, and increased levels of inflammatory cytokines, especially tumor necrosis factor (TNF), are common in human PM [4, 7, 12-14], and directly or indirectly, via impaired materno-fetal exchange of nutrients and gases and/or high metabolic demand of infiltrated leukocytes [15], contribute to poor birth outcomes [16]. These important contributions notwithstanding, the precise molecular and cellular mechanisms that lead to placental failure and fetal compromise must still be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Sequestering parasites release bioactive molecules that stimulate both maternal cells [4] and fetal syncytiotrophoblast [5, 6] to produce proinflammatory cytokines and chemokines, which in turn recruit, activate and retain inflammatory cells in the maternal intervillous space [4, 6-12]. Indeed, accumulation of maternal monocyte/macrophages, and increased levels of inflammatory cytokines, especially tumor necrosis factor (TNF), are common in human PM [4, 7, 12-14], and directly or indirectly, via impaired materno-fetal exchange of nutrients and gases and/or high metabolic demand of infiltrated leukocytes [15], contribute to poor birth outcomes [16]. These important contributions notwithstanding, the precise molecular and cellular mechanisms that lead to placental failure and fetal compromise must still be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond malaria infection, local inflammation-triggered fetal growth restriction was found in a cohort of Malawian women and their infants26. Furthermore the association between local inflammation and micronutrient transport was confirmed in an in vitro model of placental malaria with local inflammation.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore the association between local inflammation and micronutrient transport was confirmed in an in vitro model of placental malaria with local inflammation. Specifically maternal monocyte products impaired the activity of amino acid transporters on placental cells, leading to fetal growth restriction26. We have recently reported that free heme and heme-mediated signaling pathways play important roles in the pathogenesis of severe P. falciparum malaria (children/adults)27; and that elevated levels of IL-10 in maternal peripheral blood can serve as a biomarker associated with asymptomatic malaria in pregnant women28.…”
Section: Discussionmentioning
confidence: 99%
“…y por ende no desarrolla una inmunidad efectiva en comparación con las multigestantes 24 , además, la concentración de hormonas sexuales y el cortisol, tienden a disminuir a medida que aumenta la paridad 10,19,18 Fisiopatología de malaria placentaria Los eritrocitos infectados por Plasmodium spp., expresan un antígeno variante en su membrana, denominado -Plasmodium falciparum erythrocyte membrane protein 1-(PfEMP1) 25 , que facilita la adhesión de las células infectadas a receptores de condroitín sulfato A (CSA), presentes en la placenta 26 ; esta unión facilita el ingreso y secuestro del patógeno en el espacio intervelloso 27 , allí se desencadena una respuesta inmune pro-inflamatoria, mediada inicialmente por la liberación de TNF-α por parte de las células natural killer uterinas (NKu), que tiene un efecto químioatrayente sobre monocitos y macrófagos para amplificar la respuesta inmunitaria TH1 , en un intento por defender el contexto placentario contra la infección 19 .…”
Section: Malaria Y Paridadunclassified